The praise meanings and their artistic formations in AlNami's poetry (Journal of Hama University, 2025)
This study attempts to explore a group of praising meanings used by AlNami to form his poetic imagery. Although some of these meanings are common among Ancient Arab poets with some differences regarding the implementation in poetic structure, AlNami could add his personal emotions and creative vision which states that a tribe can be an important partner in praising the major character. Moreover, praising the character by sharing the poet’s true feelings towards the praised figure is one of the significant elements that established AlNami’s special praising vision.AlNami formed his praising structures and meanings with tools and techniques that determined his artistic ability and poetic vision. He integrated figurative forms such as: similes, metaphors and metonyms with soul components to reveal them. Then his linguistic elements were interrelated with deep ties and special visions.He employed distinctive rhetorical structures based on symmetrical and contrastive structures to present remarkable images showing his poetic talent which had been faded due to the loss of his poetic production. He also employed colours in contrasting or adjacent images built to reveal the intended meaning and raise the artistic value of poetic images. The study was inspired from an in-depth reading of AlNami’s poetry through his little poetic collection, which was mostly in praise of Saif Al-Dawla Al-Hamdani, as he was one of the most prominent poets of his court. The study used the descriptive analytical approach to reach the desired results, which centered around proving AlNami’s distinctive poetic ability. Although he possessed the linguistic and semantic poetic meanings of praise, he bestowed upon them from his personal ability, transparent self, and true love towards Seif AlDawla. Accordingly, his images became distinct and his meanings renewed because he owned the authority over his own construction.